2017
DOI: 10.1088/1361-6501/aa5afb
|View full text |Cite
|
Sign up to set email alerts
|

A fast procedure of stress state evaluation in magnetically anisotropic steels with the help of a probe with adjustable magnetizing field direction

Abstract: components (tanks, girders etc). The surface stress components i.e. the values and directions of the main stresses (σ 1 , σ 2) may be determined with the help of the hole drilling method, or x-ray diffraction analysis [1]. The information obtained in such a way is 'local' and the measurement time in both cases is relatively long. Being so, neither one of those methods can be recommended for the analysis of the spatial distribution of the stress state (obtaining a dense enough matrix of data in an acceptable am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In earlier works, during the study of angular dependence of the MBN response, whole signal bursts measured within a half of magnetization period were analysed. These studies showed the potential for applying the Barkhausen effect to assess magnetic anisotropy [13,16,20,22,[25][26][27]. In [24], the authors studied influence of the crystal and stress (residual and applied) anisotropy on the characteristics of maximum amplitude of the MBN envelope.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier works, during the study of angular dependence of the MBN response, whole signal bursts measured within a half of magnetization period were analysed. These studies showed the potential for applying the Barkhausen effect to assess magnetic anisotropy [13,16,20,22,[25][26][27]. In [24], the authors studied influence of the crystal and stress (residual and applied) anisotropy on the characteristics of maximum amplitude of the MBN envelope.…”
Section: Introductionmentioning
confidence: 99%
“…On the obtained sample the BN signal distribution measurements were repeated. With the help of the calibrating procedure results and after application of the computational procedure (taking into account tensor description of stress) described in detail in [5] the influence of the welding procedure on the stress distribution was assessed (it was the difference between the results obtained before and after welding). Fig.…”
Section: Results Of Measurement and Stress Calculations For The P91 Smentioning
confidence: 99%
“…Welding-induced distortions and residual stresses in stiffened panels may affect their ultimate strength. To determine the level of welding-induced residual stresses, nondestructive testing in the section located at a half-length of the 5 mm and 8 mm stiffened plates, where the maximum level is observed, was carried out employing MagStress5c apparatus developed by NNT laboratory, which utilises the Barkhausen effect [19]resulting in the full information on the stress distribution (main stress components and their orientation in all the investigated points. The welding technique has been identical for each plate.…”
Section: #mentioning
confidence: 99%